SISTEM PENDUKUNG KEPUTUSAN PENERIMA BANTUAN LANGSUNG TUNAI (BLT) MENGGUNAKAN METODE TOPSIS DAN SAW (STUDI KASUS DI KANTOR LURAH LIMBUNGAN) - Rendi Haryono Septy; Mariza Devega (Universitas Lancang Kuning, 2022)
Cash Direct Assistance is a government assistance program in the form of providing cash or various other assistance for the poor. The Limbungan sub-district has an important role in the proverty management program and has a role in the selection of BLT recipient candidates. However, in its implementation, there is still a form ofsubjectivity in the determination of prospective BLT recipients because the data for prospective recipients is a recommendation of the local household that is reported to the Limbungan sub-district and selected based on considerations without an accurate assessment. Likewise, the quota for BLT recipients from the government is not comparable to the list of BLT recipients submitted by the local RT. In this case, there is a need for a decision support system to find out who really deserves to receive BLT so that the allocation of BLT funds is right on target in accordance with predetemined criteria. The criteria used in this study are income, expenses, number of dependents, number of family members of productive age, residence status, house area, and land area. The sample used is 5 people who recommend direct cash assistance is more targeted because it is based on the weight of the criteria that have been determined, so that accurate result will be obtained.